Identification and Ranking of Cloud-Based Applications in E-Learning of Afghanistan: A Case of Public Universities - Musawi, Sayed Zabihullah; Baktash, Jawid Ahmad (Elsya : Journal of English Language Studies, 2021)
Cloud-based Applications are suitable tools in the E-learning system, and they bring the most facilities in E-learning due to availability and on-demand self-services. During Covid-19 lockdown, while presential learning stopped and E-learning started. The Ministry of Higher Education has begun E-learning in public and private universities. Therefore, Afghanistan’s universities used Cloud-based Apps in E-learning, but these Apps are not identifying and ranking in the E-learning of Afghanistan. This study aims to identify and rank the Cloud-based Apps in terms of usefulness and effectiveness in E-learning using state-of-the-art, and its usage in public universities of Afghanistan. To get an accurate answer to the defined questions, mixed research was used. Therefore, an online questionnaire was distributed randomly to six public universities in six different parts of Afghanistan. The respondents were divided into two categories (lecturers and students) and asked to respond to Cloud-based Apps usage and effectiveness in E-learning. The responses were analySed using Chi-Square Tests. The result showed the most, low, and lowest useful Cloud-based Apps in E-learning. In conclusion, the research finding showed that Google Classroom was the most LMS, WhatsApp was the most mobile instant messaging, Gmail was the most E-mail server and Skype was the most video conferencing Cloud-based Apps in E-learning in most public universities of Afghanistan.